Evaluation of a Three-Stage Method for Improving Mandibular Retrognathia with Labially Inclined Incisors Using Genioplasty, Segmental Osteotomy, and Two-Jaw Surgery - Kazuhiro Matsushita; Hiro-o Yamaguchi; Mino Koshikawa-Matsuno; Nobuo Inoue (Case Reports in Medicine)
We have sometimes encountered difficulty in improving labially inclined teeth, particularly in patients with mandibular retrognathia, because the symphysis menti is often thin and insufficient space is available to permit sagittal rotation of the teeth without root exposure from the alveolar bone. We have previously described a three-stage method to overcome this problem, involving genioplasty for improving the retruded chin, and to construct the infrastructure for subsequent subapical segmental alveolar osteotomy, subapical segmental alveolar osteotomy itself, and, finally, two-jaw surgery. Bone augmentation with thin cortical bone at the gap created on the upper surface of the advanced genial segment was also addressed in the previous report. In the present study, to confirm the benefits of the three-stage method using objective data, cephalometric evaluation was performed in each step. In all cases, pogonion (Pog) was moved forward substantially. Net linear forward movement of Pog and net changes in SN-Pog were from 12 mm to 20 mm and from 4.8° to 7.0°, respectively. Angle of mandibular incisors and interincisal angle also improved to desirable levels. Although this method requires three separate surgeries, the approach safely improves the clinical situation and accentuates treatment efficacy.